The Students’ Voice on the Potential Contribution of ChatGPT-integrated Debate Coursebook: Matter, Manner, and Method - Suciati; Novia Trisanti; Yudhi Arifani; Zulfa Sakhiyya (Langkawi: Journal of The Association for Arabic and English, 2026)
Although ChatGPT is commonly used to improve writing skills, its potential to improve speaking, especially English debate, remains understudied. This study aims to explore students' perceptions on the contributions of the Debate Coursebook with ChatGPT-supported learning activities for studying Matter (content), Manner (delivery, confidence, and pronunciation), and Method (structure, flow, rebuttal, and Point of Information). This qualitative research focuses on exploring the experiences of 10 students performing as debaters, moderator, timer, adjudicator, and audience through the interview, documentation, and observation. Each participant was given a unique code to guarantee anonymity and preserve the confidentiality of their identities throughout the research process, and the gathered data was examined using a thematic analysis technique. This technique was implemented to identify how they learn matter, manner, and method aspects (Freeley & Steinberg theory). The results showed that in the matter aspect, ChatGPT helped students construct more logical and relevant arguments, but some felt overly dependent on AI suggestions. For manner aspect, it is contributive for pronunciation, intonation, and confidence. Meanwhile, for method aspect, the debate structure and rebuttal skills became clearer, although some still had difficulty adapting the flow to the real-life debate format. ChatGPT-integrated debate coursebook is contributive for debate practice, especially big class, but it must be under the lecturer guidance. Instructors are advised to integrate ChatGPT as a supporting tool, not a replacement for conventional debate practice.